Students Attitudes and Hesitancy Toward COVID-19 Vaccine: A Cross-Sectional Study: Sikap dan Keraguan Mahasiswa Terhadap Vaksin COVID-19: Sebuah Studi Cross-Sectional - Jassim, Firas A. (Indonesian Journal on Health Science and Medicine, 2024)
Background: Recovering from the recent COVID-19 outbreak requires widespread vaccine coverage. Nonetheless, there are worries regarding the effectiveness and safety of this immunization campaign. Objectives: To identify students’ attitudes and hesitancy toward COVID-19 vaccine. Methods: Data for a cross-sectional study with 200 participants from the University of Basrah was gathered using a closed-ended questionnaire. The participants ranged in age from 18 to 58. The study began in November 2021 and ended in April 2022. Utilizing SPSS version 26, the analysis was conducted. Results: According to the report, 84% of those surveyed had received the coronavirus vaccine. The Pfizer vaccine was selected by 73% of them. (61%) of the participants' trust in the vaccine's manufacturer. According to medical studies, 82.5% of participants said they would rather get the vaccine. Conclusion: The negative effects of the immunizations and their administration caused a great deal of anxiety. Social media has a big impact on the decision to get the immunizations. Highlights: Assess students' attitudes and hesitancy toward COVID-19 vaccines. Cross-sectional study with 200 participants; SPSS version 26 analysis. High vaccination rates, Pfizer preference, trust influenced by social media. Keywords: Students, Attitudes, Hesitancy, COVID-19 Vaccine